Timurid Princesses: Historical Figures And Political Role (Eurasian Research Bulletin, 2025)
This article, based on historical sources, illuminates the lives, political activities, spiritual legacies, and roles in state affairs of renowned princesses who lived during the Timurid dynasty - Sultan Bakht Begum, Gavhar Shod Begum, Shodmulk Khatun, and Khanzada Begum. Each of these women actively participated in the socio-political life of their era, with some playing crucial roles in state governance. The princesses' selfless service, wisdom, determination, and tragic fates provide important historical evidence for understanding the complex socio-political landscape of the Timurid period. Through this article, readers will become acquainted with these Timurid princesses as exemplars of the highly intellectual and resilient women of their time.